What do we actually know about exosomal microRNAs in kidney diseases? - Li, Qianyu; Zhang, Zhiping; Yin, Min; Cui, Cancan; Zhang, Yucheng; Wang, Yali; Liu, Feng (Frontiers in Physiology, 2022)
There are several types of kidney diseases with complex causes. If left untreated, these diseases irreversibly progress to end-stage renal disease. Thus, their early diagnosis and targeted treatment are important. Exosomes—extracellular vesicles released by a variety of cells—are ideal carriers for DNA, RNA, proteins, and other metabolites owing to their bilayer membranes. Studies have shown that almost all renal cells can secrete exosomes. While research on exosomal microRNAs in the context of renal diseases begun only recently, rapid progress has been achieved. This review summarizes the changes in exosomal microRNA expression in different kidney diseases. Thus, it highlights the diagnostic and prognostic value of these exosomal microRNAs. Further, this review analyzes their roles in the development of different kidney diseases, guiding research on molecular mechanisms and therapeutic strategies.